(untitled) (Huellas, 2025)
The article reflects on the uses and meanings that inhabitants of an expanding area of the city of Mar del Plata give to the concept of “community”. The selected population belongs to inhabitants who have recently settled in the area through practices of houses self-building by using non-conventional materials for construction. The territory is part of the Paseo Costanero Sur of the city, where I carried out fieldwork from a qualitative perspective through in-depth interviews with self-builders and participant observation of the construction processes. In a context of disputes and conflicts over territory, and in which opposing urbanization models are put into play, the concept “community” translates the ways in which new residents shape and produce fragments of the city, how they make decisions and dispute the territory, while they reshape their way of living, assigning a community and sustainable sense to it. These values go through and explain the decisions of who can inhabit the area and how they can do it. In doing so, they reconfigure rights, possibilities and identities, in contrast to the capitalist urbanization model.